Factors associated with successful chronic disease treatment plans for older Australians: Implications for rural and Indigenous Australians. (29th January 2019) - Holdsworth, Stuart; Corscadden, Lisa; Levesque, Jean‐Frederic; Russell, Grant
Abstract: Objective: To identify factors associated with having a successful treatment plan for managing chronic conditions. Design: Secondary analysis of the Commonwealth Fund's 2014 International Health Policy Survey. Setting: Australia 2014. Participants: A total of 3310 Australian adults over 55 years old. Main outcome measures: Whether respondents: (i) had a treatment plan for their chronic condition; and (ii) believed that the plan was helpful in managing their condition. Methods: We used multiple logistic regressions to assess the association between individual factors (age, income, remoteness, Australian Aboriginal or Torres Strait Islander status) and patient reports of the outcomes of interest. Results: Most respondents reported having a treatment plan for their chronic condition(s); the majority reported that it was helpful in managing their health. Treatment plan provision was associated with age over 75 years, above‐average income, Australian Aboriginal or Torres Strait Islander status and multiple chronic conditions. Plans were less likely for residents of outer regional and remote areas. Indigenous respondents were far less likely than non‐Indigenous respondents to report that their treatment plan helped a lot. Respondents with providers who 'always' explained things were far more likely to say that a treatment plan helped. Conclusion: While the patient–provider relationship influenced the perceived success of treatment plans, inequities in treatment plan provision seemed linked with rurality and income. The higher frequency of treatment plans for Indigenous respondents might reflect access to Australian Aboriginal or Torres Strait Islander health checks, while the plan's perceived lack of efficacy suggests a gap in cultural acceptability.